Sistemas agroalimentares de base agroecológica: caracteres morfofisiológicos e produtivos de tuberosas (Ipomoea batatas e Dioscorea alata) adubadas com complexos orgânicos líquidos - Luna, Túlio de Melo (2022)
As time goes by, it becomes more evident, that agri-food arrangements are emerging as the main power, which will support the fundamental transformations of the planet. The objective of the research was to evaluate organic and mineral fertilization on production and gas exchange in yam and sweet potato crops. The research was conducted in the field, under dryland conditions, from January to September 2021, in the village of Cupissura, municipality of Caaporã-PB. Two experiments were installed, the first with sweet potato culture and used a triple factorial (2x5x3), corresponding to the use of two sources of organic complexes, five doses (0; 1.5; 03; 4.5 and 06 L ha-1) and three spacings (20, 30, and 40 cm respectively) with four repetitions. In the second experiment the crop analyzed was the yam São Tomé (Dioscorea alata), in a randomized block experimental design, in factorial scheme (2x5) + 2, with four repetitions, corresponding to the planting of the dimpled seed (mamita) with five doses of organic complex fertilization (0; 5; 10; 15; 20 L ha-1, with and without the use of manure, plus the additional treatments T11 - Commercial seed, with manure and 10 L ha-1 of the organic complex; T12 - Commercial seed, with manure and NPK. Net photosynthesis (A), stomatal conductance (gs), transpiration (E), intercellular CO2 concentration (Ci), intercellular and extracellular CO2 concentration (Ci/Ca), water use efficiency (WUE), intrinsic water use efficiency (iWUE) were determined using an infrared gas analyzer (IRGA®). The biophysical variables were submitted to variance analysis, whose results show that there was interaction between the forms of application and doses of organic complexes for the variables (A), (gs), (E), (Ci), (Ci/Ca), (WUE), (iWUE), Length, Diameter, PTP, PC. Fertilization with the organic complexes, in this research, proved to be more efficient for the production of food tubers than with the additional treatment with NPK.